1997
DOI: 10.1161/01.hyp.30.5.1047
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin Release by Rat Cardiac Fibroblasts

Abstract: Cardiac fibroblasts, as the source of extracellular matrix for the left ventricle, subserve important functions to cardiac remodeling and fibrotic development following myocardial infarction or with pressure-overload cardiac hypertrophy. The fibroblast may be the target cell for angiotensin-converting enzyme inhibitors (ACEI) that are cardioprotective and reverse collagen deposition and remodeling but whose mechanisms of action remain controversial. Because we previously documented phenotypic differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
38
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 43 publications
4
38
0
Order By: Relevance
“…22 PGE 2 inhibits collagen production by several mechanisms, including reduction in the uptake of proline, inhibition of collagen gene expression, and a decrease in collagen types I and III mRNA levels. 23,24 Furthermore, PGF 2␣ has been shown to be released from cells after experimental infarction and to stimulate hypertrophic growth. 25 It was recently reported that the pharmacological blockade of AT 2 potentiated the Ang II-induced production of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…22 PGE 2 inhibits collagen production by several mechanisms, including reduction in the uptake of proline, inhibition of collagen gene expression, and a decrease in collagen types I and III mRNA levels. 23,24 Furthermore, PGF 2␣ has been shown to be released from cells after experimental infarction and to stimulate hypertrophic growth. 25 It was recently reported that the pharmacological blockade of AT 2 potentiated the Ang II-induced production of PGE 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the changes in myocardial structure inhibit myocardial diastolic and systolic function, resulting in cardiac dysfunction [26,27]. The effects of BPS, such as coronary circulation improvement, myocardial and vascular protection [19] and its anti-fibrosis effect on myocardial interstitium [30], have been demonstrated previously. However, the effects of BPS on hemodynamics, cardiac function and myocardial contractility in patients in the hypertrophic phase have not been clarified.…”
mentioning
confidence: 99%
“…These include inhibitory effects of PGI 2 and its analogue on angiotensin II-induced hypertrophy in cultured cardiomyocytes 12 and their inhibitory effects on proliferation and collagen synthesis in cultured cardiac fibroblasts. 13 In addition, synthesis of PGE 2 and PGI 2 has been reported to be elevated in the hypertrophied and failing heart 14,15 along with an upregulation of cyclooxygenase (COX)-2. 16 The hypertrophic effect of exogenously administered PGF 2 ␣ on cardiomyocytes has also been reported.…”
mentioning
confidence: 99%